Potential of Local Plants as Sources of Iron, Folic Acid, and Calcium for Preconception Supplementation - Nur Cholila; Nur Maziyah Hurin’in; Tri Yunita Fitria Damayanti (Universitas Wijaya Kusuma Surabaya, 2026)
Background: High prevalence of anemia and nutritional deficiencies among Women of Childbearing Age in Indonesia, including Tuban Regency, elevates pregnancy complication risks. Crucial micronutrient supplementation (iron, folic acid, calcium) often overlooks local resources. This study uniquely identifies Tuban's local plants as simultaneous sources of these three vital micronutrients, moving beyond conventional supplements. Objective: To identify and analyze the iron, folic acid, and calcium content of local plants in Tuban for preconception supplementation. Methods: This descriptive quantitative study analyzed dried powder samples from five local leaf species: katuk, sweet potato, moringa, cassava, and spinach. Iron and calcium were measured by AAS, and folic acid by HPLC, in an accredited laboratory. Data were descriptively analyzed and compared with the WCA Recommended Dietary Allowances (RDA) and the Indonesian Food Composition Table (TKPI) 2017. Results: Moringa leaves (Moringa oleifera) were an exceptional source of iron (28.04 mg/100g) and calcium (1783 mg/100g), significantly exceeding WCA RDA. Sweet potato leaves (Ipomoea batatas) emerged as the best folic acid source (1.59 mg/100g), meeting WCA RDA with a small serving (25g). Spinach and katuk leaves also contributed to iron and folate intake. Micronutrient concentrations in dried powder generally surpassed TKPI 2017 fresh leaf data. Conclusion: Local plants, particularly moringa and sweet potato leaves, offer substantial potential as sustainable, economical, and culturally relevant sources of iron, folic acid, and calcium for preconception supplementation, thereby enhancing women's reproductive health in Tuban Regency.